Antiviral response is not sustained after cessation of lamivudine treatment in chronic hepatitis B patients: A 10‐year follow‐up study. Issue 5 (23rd December 2016) - Kang, Seong Hee; Kang, Keunhee; Jong Eun, Yeon; Lee, Young Sun; Kim, Tae Suk; Yoo, Yang Jae; Suh, Sang Jun; Yoon, Eileen L.; Jung, Young Kul; Kim, Ji Hoon; Seo, Yeon Seok; Yim, Hyung Joon; et al.
Abstract : Although the ideal end point for antiviral treatment in patients with chronic hepatitis B (CHB) is loss of HBsAg, the typical clinical end points are HBeAg seroconversion in HBeAg‐positive patients and long‐term DNA suppression in HBeAg‐negative patients. We evaluated the long‐term antiviral response after cessation of lamivudine treatment in CHB patients. A total of 157 patients who had discontinued lamivudine between 1997 and 2014 were enrolled (97 HBeAg‐positive and 60 HBeAg‐negative CHB patients). The long‐term durability of the antiviral response (viralogical relapse; HBV DNA ≥10 4  copies/ml) and the clinical course of these patients were analyzed retrospectively. In HBeAg‐positive patients, the mean follow‐up period after discontinuation was 72.3 months. The cumulative probabilities of virological relapse at 1, 12, 24, 48, 60, 96, and 120 months were 10.3%, 40.2%, 55.6%, 62.8%, 65.9%, 67.0%, and 67.0%, respectively. In HBeAg‐negative patients, the cumulative probabilities of a virological relapse at 1, 12, 24, 48, 60, 96, and 120 months were 25.0%, 35.0%, 41.7%, 43.3%, 43.3%, 46.7%, and 48.3%, respectively. Younger age (HR 1.732, 95%CI: 1.058–2.835, P  = 0.02) was predictive of non‐virological relapse in HBeAg‐positive patients. And achievement of undetectable HBV DNA level within 3 months of treatment discontinuation was associated with decreased rate of virological relapse (HR 0.159, 95%CI: 0.069–0.367 P  < 0.01) in HBeAg‐negative patients. Despite meeting the requirements for treatment discontinuation, approximately half of the CHB patients treated with lamivudine relapsed. Thus, the antiviral response is not reliably sustained after lamivudine treatment cessation. J. Med. Virol. 89:849–856, 2017 . © 2016 Wiley Periodicals, Inc.